2015
DOI: 10.1016/j.chemgeo.2014.11.019
|View full text |Cite
|
Sign up to set email alerts
|

An optimized method for stable isotope analysis of tree rings by extracting cellulose directly from cross-sectional laths

Abstract: a b s t r a c tStable isotopes in tree-ring α-cellulose are valued as environmental proxies and their use is steadily increasing; however, preparation of α-cellulose is a bottleneck in isotope analysis. Recent methodological breakthrough for extracting tree-ring α-cellulose directly from tree-ring cross-sectional laths drastically increased the throughput of tree-ring isotope data. In this paper, we evaluate our recently designed "cross-section" method. This method employs polytetrafluoroethylene (PTFE) cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 50 publications
3
47
0
1
Order By: Relevance
“…All sampled trees were older than 70 years to avoid the effect of juvenile wood on the carbon isotope ratios (Leavitt, ). The holocellulose extraction followed the procedures described by Schollaen, Baschek, Heinrich, and Helle () applying a novel cross‐section extraction method, which is a re‐design of the technique proposed by Kagawa, Sano, Nakatsuka, Ikeda, and Kubo (). The main advantage of this technique is the time reduction invested in each sample since it allows the cellulose extraction of different rings at the same time.…”
Section: Methodsmentioning
confidence: 99%
“…All sampled trees were older than 70 years to avoid the effect of juvenile wood on the carbon isotope ratios (Leavitt, ). The holocellulose extraction followed the procedures described by Schollaen, Baschek, Heinrich, and Helle () applying a novel cross‐section extraction method, which is a re‐design of the technique proposed by Kagawa, Sano, Nakatsuka, Ikeda, and Kubo (). The main advantage of this technique is the time reduction invested in each sample since it allows the cellulose extraction of different rings at the same time.…”
Section: Methodsmentioning
confidence: 99%
“…Although using whole wood (bulk wood) for isotopic analyses is reportedly acceptable, uncertainties regarding the analysis of whole wood remain (Loader et al 2003;Ferrio and Voltas 2005;Verheyden et al 2005b), especially for analysis at intra-annual scales. In addition, a recent advance has allowed the extraction of α-cellulose directly from cross-sectional laths before the subdivision of tree rings (Li et al 2011;Xu et al 2011;Kagawa et al 2015). Therefore, we used α-cellulose for isotope analysis and applied the cross-section method proposed by Kagawa et al (2015) for the extraction.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In addition, a recent advance has allowed the extraction of α-cellulose directly from cross-sectional laths before the subdivision of tree rings (Li et al 2011;Xu et al 2011;Kagawa et al 2015). Therefore, we used α-cellulose for isotope analysis and applied the cross-section method proposed by Kagawa et al (2015) for the extraction. The chemical protocol was based on the Jayme and Wise method (Green 1963) modified for α-cellulose extraction (Mullane et al 1988;Loader et al 1997;Xu et al 2011).…”
Section: Sample Preparationmentioning
confidence: 99%
“…The analytical precision of a laboratory working standard (Merck cellulose; Darmstadt, Germany) measurement was about 0.15‰ (1 σ ). The oxygen isotopic analyses for the other two wood disks (167 and 179 years old) were conducted at RIHN, using a “cross‐section” method for α ‐cellulose extraction [ Kagawa et al , ]. This method extracts α ‐cellulose not from individual rings but directly from a 1 mm thick tree ring plate.…”
Section: Methodsmentioning
confidence: 99%
“…The tree ring cellulose samples were then cut from the α ‐cellulose plate, weighted, and wrapped into silver foil. Kagawa et al [] found no significant difference between the δ 18 O values determined by the cross‐section method and those determined by the conventional method. This method has already been applied to several species [e.g., Xu et al , , ; Sano et al , ; Xu et al , ].…”
Section: Methodsmentioning
confidence: 99%